Allergen Skin Test Reactivity and Serum Total IgE Level in Adult Bronchial Asthmatic Patients - Parveen, Tasmina; Begum, Noorzahan; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2009)
Background: Asthma affects more than 100 million people worldwide. Increased morbidity is multifactorial and may include increased exposure to indoor allergens and environmental pollutants, overuse of beta-2 agonist, underuse of anti-inflammatory mediators and limited education about health care. Allergy represents a specific alteration in biologic reactivity mediated by an immunologic mechanism and resulting in an adverse physiologic response. Objective: Some of the type of allergen's sensitivity by skin prick test and serum total IgE level were studied in adult asthmatic patients to observe their relationships. Methods: This study was carried out in the department of Physiology, Bangabandhu Sheik Mujib Medical University, Dhaka and Asthma center,Mohakhali, Dhaka from January 2005 to December 2005. Allergen skin prick tests (SPT) were done by Pepy's skin prick method and serum total IgE level by Enzyme Linked Immunosorbent Assay method on 30 asthmatic patients and 30 age and sex matched control subjects. Data were analyzed statistically by unpaired student's ‘t' test and Chi- squares test. Results: In this study, maximum numbers of asthmatic patients had positive SPT for dust mite which was followed by house dust and by cockroach. Frequency percentage for dust mite was significantly higher (P<0.05) than that of house dust and cockroach. It was also significantly higher in house dust than that of cockroach (P< 0.001). The mean serum total IgE level was significantly higher (P<0.001) in asthmatic adults compared to that of healthy subjects. On the other hand, the association between the positive skin prick tests of all allergens used in this study and elevated serum total IgE were not statistically significant (P >0.05). Conclusion: Therefore , it can be concluded that different allergens like, house dust, dust mite and cockroach are responsible for bronchial asthma in our country which can be detected by SPT. Thus it can be used for identification of type of actual allergens responsible for bronchial asthma which may be a useful measure for earlier detection of allergens and for hyposensitization or desensitization of that patients accordingly with those allergens. Key words: Allergen, IgE, Bronchial asthma. DOI: 10.3329/jbsp.v4i1.4062 J Bangladesh Soc Physiol. 2009 June; 4(1): 1-6